Essays on Babylonian and Biblical Literature and Religion - Abusch, Tzvi, (Harvard Semitic Studies ;, 2020)
In this volume, Tzvi Abusch presents studies written over a span of forty years that were completed prior to his retirement from Brandeis University in 2019. They reflect several themes that he has pursued in addition to his work on witchcraft literature and the Epic of Gilgamesh. The volume begins with general articles on Mesopotamian magic, religion, and mythology; these are followed by a set of articles on Akkadian prayers, especially šuillas , focusing, first of all, on exegetical and linguistic (synchronic) studies and, then, on diachronic analyses; part two contains a series of literary studies of Mesopotamian and biblical classics; part three is devoted to comparative studies of terms and phenomena; finally, the fourth part takes up texts that are of legal interest. The Harvard Semitic Studies series publishes volumes from the Harvard Museum of the Ancient Near East. Other series offered by Brill that publish volumes from the Museum include Studies in the Archaeology and History of the Levant and Harvard Semitic Monographs , https://hmane.harvard.edu/publications .